2004
DOI: 10.1097/00005537-200406000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of β‐Blocker Premedication on the Surgical Field During Endoscopic Sinus Surgery

Abstract: Although "optimum" conditions were present in the patients receiving beta-blocker, the authors thought that the grading system was not discriminating enough to demonstrate a significant difference between the groups. The crucial finding in the study was the correlation between heart rate and surgical grade in the entire group. During endoscopic sinus surgery surgery, anesthetic manipulations should be directed at maintaining a low heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
169
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(186 citation statements)
references
References 20 publications
6
169
1
3
Order By: Relevance
“…However, vasoactive drugs cannot reduce the FESS bleeding when MAP was controlled at level of 65-75 mmHg (17); conversely, vascular dilation caused by the drug would increase surgical bleeding and has a negative impact on the surgical field (14). Previous studies have demonstrated a significant correlation between the HR and surgical field bleeding during surgery (18)(19)(20). Compared with nitroglycerin, esmolol reduces bleeding by slowing down HR and offering an improved surgical approach with only minimal reduction in MAP (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, vasoactive drugs cannot reduce the FESS bleeding when MAP was controlled at level of 65-75 mmHg (17); conversely, vascular dilation caused by the drug would increase surgical bleeding and has a negative impact on the surgical field (14). Previous studies have demonstrated a significant correlation between the HR and surgical field bleeding during surgery (18)(19)(20). Compared with nitroglycerin, esmolol reduces bleeding by slowing down HR and offering an improved surgical approach with only minimal reduction in MAP (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been designed to reduce bleeding during surgery, none of these techniques have consistently provided a desirable bloodless field for the surgeon. So to provide optimal field hypotensive agents given such as sodium nitroprusside, nitroglycerine, propofol, clonidine, esmolol, metoprolol & atenolol had been used individually to decrease blood loss in FESS [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al are of the opinion that intraoperative bleeding is dependent on many factors, of which advanced underlying disease, arterial hypertension, blood clotting disorders and heart diseases are the most significant [22]. Similarly, Cassano et al demonstrated a relationship between arterial hypertension and a higher risk of perioperative bleeding.…”
Section: Discussionmentioning
confidence: 99%